Determinants Influencing Micro, Small, and Medium Enterprises (MSMEs) Decisions to Pursue Halal Certification - Bahrudin, Moh; Iqbal, Muhammad; Saefurrohman, Ghina Ulfa; Walsh, John (UIN Sunan Gunung Djati Bandung, 2025)
Understanding the factors that influence Micro, Small, and Medium Enterprises (MSMEs’) to obtain halal certification is important because it can help increase their participation, strengthen consumer trust, and promote sustainable growth in the halal sector. This study aims to analyze the determinants influencing MSMEs’ decisions to pursue halal certification, focusing on five critical factors: consumer awareness, regulatory processes, trust and reputation, economic considerations, and religiosity. Employing a quantitative explanatory research design, supplemented by qualitative interviews, data were collected from 100 MSMEs’ operating in the food, beverage, cosmetics, and fashion sectors. All constructs showed high validity and reliability, with Cronbach’s Alpha ranging from 0.783 to 0.828 and item-total correlations above 0.30, while the Kolmogorov–Smirnov test confirmed that the residuals followed a normal distribution. Additionally, Variance Inflation Factor (VIF) and tolerance values indicated no multicollinearity among the independent variables, and the Glejser test showed no heteroskedasticity, supporting the regression model’s validity and reliability. The results indicate that consumer awareness (β = 0.308, p < 0.01), regulatory processes (β = 0.153, p < 0.05), trust and reputation (β = 0.204, p < 0.05), and religiosity (β = 0.249, p < 0.01) significantly and positively influence MSMEs’ decisions to pursue halal certification, while economic factors (β = 0.020, p = 0.764) have no significant effect. The study concludes that consumer awareness, regulatory process, trust, and religiosity influence MSMEs' decisions to pursue halal certification.